2017
DOI: 10.1186/s12885-017-3394-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of oral ridaforolimus in combination with paclitaxel and carboplatin in patients with solid tumor cancers

Abstract: BackgroundRidaforolimus is a mammalian target of rapamycin inhibitor that has activity in solid tumors. Paclitaxel and carboplatin have broad antineoplastic activity in many cancers. This phase I trial was conducted to determine the safety profile, maximal tolerated dose, and recommended phase II dose and schedule of oral ridaforolimus combined with paclitaxel and carboplatin in patients with solid tumor cancers.MethodsEligible patients with advanced solid tumor cancers received oral 10 to 30 mg ridaforolimus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In a phase I/II clinical trial of everolimus combined with gemcitabine/cisplatin for metastatic triple negative breast cancer, the combination treatment did not have synergistic effects despite the majority of patients harboring PIK3CA mutations [269]. The combination of ridaforolimus with paclitaxel and carboplatin in a phase I study in patients with solid tumor cancers showed antineoplastic activity with no unanticipated toxicities [266]. In a randomized phase II study to compare the effects of monotherapy with vinorelbine, which disrupts microtubules, versus combined vinorelbine and everolimus for second-line chemotherapy in advanced HER2-negative breast cancer, the combined therapy was not superior to the monotherapy, although the treatment was well tolerated [270].…”
Section: Combining Mtor Inhibition With Conventional Chemotherapies Amentioning
confidence: 99%
“…In a phase I/II clinical trial of everolimus combined with gemcitabine/cisplatin for metastatic triple negative breast cancer, the combination treatment did not have synergistic effects despite the majority of patients harboring PIK3CA mutations [269]. The combination of ridaforolimus with paclitaxel and carboplatin in a phase I study in patients with solid tumor cancers showed antineoplastic activity with no unanticipated toxicities [266]. In a randomized phase II study to compare the effects of monotherapy with vinorelbine, which disrupts microtubules, versus combined vinorelbine and everolimus for second-line chemotherapy in advanced HER2-negative breast cancer, the combined therapy was not superior to the monotherapy, although the treatment was well tolerated [270].…”
Section: Combining Mtor Inhibition With Conventional Chemotherapies Amentioning
confidence: 99%
“…mTOR inhibitors have also been combined with chemotherapy. Two phase 1 trials in solid tumors using CT with either ridaforolimus [ 121 ] or temsirolimus [ 122 ] showed response rates of 25% and 82%, respectively, in EC populations. However, a randomized phase 2 trial (GOG-86P) comparing CT with either temsirolimus or bevacizumab or carboplatin plus ixabepilone and bevacizumab to CT showed improved OS when bevacizumab, but not temsirolimus, was added to CT [ 90 ].…”
Section: Reviewmentioning
confidence: 99%
“… 187 – 189 Ridaforolimus is another intravenous mTORC1 inhibitor, administrated at a dose of 12.5 mg daily for 5 consecutive days every 2 weeks, showing a modest therapeutic efficacy as a single agent. 190 A phase II trial studied the efficacy and tolerability of ridaforolimus in recurrent and advanced EC with an ORR of 8.8% and a SD of 52.9%. 191 Everolimus, an oral mTORC1 inhibitor (10 mg daily), was evaluated in a phase II study (NCT00087685) for the treatment of patients with recurrent or persistent EC, showing an ORR of 0% and a SD of 43%.…”
Section: Methodsmentioning
confidence: 99%